Nutritional composition of Tripsacum laxum fertilized with nitrogen, phosphorous and potassium - Boschini-Figueroa, Carlos; Vargas-Rodríguez, Claudio Fabián (Agronomía Mesoamericana, 2018)
Getting to know the knowledge that cultural practices have allows researchers to obtain the greatest benefit from the potential of fodder sources, this knowledge is necessary for animal production success. The aim of this study was to explore the bromatological response of Tripsacum laxum to fertilization with different levels of nitrogen, phosphorus, and potassium that were applied to the ground. The investigation was conducted at the “Alfredo Volio Mata” Experimental Dairy Farm a Dairy farm that is part of the University of Costa Rica and that is located in Ochomogo, Cartago, Costa Rica. In the investigation a randomized block design with four replications and treatments arranged in a factorial central composite and on a rotatable 53 was used. Dry matter, crude protein, neutral detergent fiber, and ether extract were determined. Depending on the levels of fertilization with N, P, and K, the appropriate doses were obtained in order to reach the maximum nutrient contents in each of the bromatological parameters evaluated in this study, it was possible to optimize the composition of the fertilizer mixture based on the nutritional component to be particularly favored, either on the leaf, on the stem, or on the whole plant. No single fertilizer dose was able to improve all nutritional components of the plant.